Effect of SIRT1 on white matter neural network in adolescent patients with depression - Ji, Ling; Jiang, Wen; Liu, Daiyan; Hou, Kaiwen (Frontiers in Psychiatry, 2022)
Background: This study aimed to explore the correlation between the rs12415800 polymorphism of the silent information regulator 1 (SIRT1) gene and the white matter neural circuit in adolescent patients with depression. Methods: We enrolled 119 participants, comprising 59 adolescent patients with depression and 60 matched healthy controls for analysis. Patients were further subdivided based on genotype; GG, AG, and AA, with G representing the wild type gene, and A representing the A allele at rs12415800. Results: We found that: (1) lower anisotropy fraction (FA) values in the left cingulate fasciculus and left anterior thalamus radiation in the AG/AA genotype were more likely to be affected by depression. (2) The FA values of the right inferior occipital-frontal fasciculus, right corticospinal tract, right inferior longitudinal fasciculus, and right superior longitudinal fasciculus regions in the depression (AG/AA) group were lower than in the depression (GG) group. (3) FA values of the right inferior occipital-frontal fasciculus left corticospinal tract, right inferior longitudinal fasciculus, left anterior thalamus radiation, right superior longitudinal fasciculus, left inferior longitudinal fasciculus, left uncinate fasciculus, and right anterior thalamus radiation in the depression (GG) group were lower than the control (GG) group. Conclusions: The polymorphism locus of the SIRT1 gene rs12415800 may be related to changes in the microstructure of white matter fiber tracts, and patients carrying the A allele (AG/AA) have more changes in the white matter than those with the non-A allele (GG).